2019
DOI: 10.1002/adfm.201902502
|View full text |Cite
|
Sign up to set email alerts
|

The Biaxial Strain Dependence of Magnetic Order in Spin Frustrated Mn3NiN Thin Films

Abstract: Multicomponent magnetic phase diagrams are a key property of functional materials for a variety of uses, such as manipulation of magnetization for energy efficient memory, data storage, and cooling applications. Strong spin-lattice coupling extends this functionality further by allowing electricfield-control of magnetization via strain coupling with a piezoelectric. Here this work explores the magnetic phase diagram of piezomagnetic Mn 3 NiN thin films, with a frustrated noncollinear antiferromagnetic (AFM) st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 30 publications
1
30
0
Order By: Relevance
“…Further, we note that in the related compound Mn 3 GaN calculations by Zemen et al [78] have shown that a combination of strain and temperature leads to a stabilization of a ferrimagnetic ground state. A similar behaviour was recently also experimentally observed for a Mn 3 NiN film on a SrTiO 3 substrate [79]. In passing we note also that epitaxial strain in Mn 3 XN as well as in Mn 3 X (X=Rh, Ir, Pt) is accompanied by a significant net magnetization in the NC ground state, albeit smaller than the one predicted for Mn 3 SnN [80].…”
Section: Discussionsupporting
confidence: 89%
“…Further, we note that in the related compound Mn 3 GaN calculations by Zemen et al [78] have shown that a combination of strain and temperature leads to a stabilization of a ferrimagnetic ground state. A similar behaviour was recently also experimentally observed for a Mn 3 NiN film on a SrTiO 3 substrate [79]. In passing we note also that epitaxial strain in Mn 3 XN as well as in Mn 3 X (X=Rh, Ir, Pt) is accompanied by a significant net magnetization in the NC ground state, albeit smaller than the one predicted for Mn 3 SnN [80].…”
Section: Discussionsupporting
confidence: 89%
“…Meanwhile, Boldrin et al systematically researched the interface‐induced strain effects on antiferromagnetic Mn 3 NiN thin films by growing it on different substrates 78,79. It was found that under biaxial or uniaxial strain, the symmetry of the antiperovskite structure ( Figure a) could be destroyed, which leads to changes in the Néel temperature (Figure 7b) and magnetization (Figure 7c).…”
Section: Electric‐field Control Of Antiferromagnetic Spintronic Devicesmentioning
confidence: 99%
“…Although the anomalous Hall effect in noncollinear antiferromagnets is of interest due to the exotic Berry curvature and in principle, the anomalous Hall resistance could be harnessed for information encoding in memory devices, the susceptibility of canted moments to magnetic fields in noncollinear antiferromagnets leads to the fact that the anomalous Hall resistance can be easily disturbed by external magnetic fields. Moreover, the electric‐field‐controlled anomalous Hall effect in noncollinear antiferromagnets has not been maturely realized at room temperature 20,78,79,81. Instead, the piezoelectric‐strain controlled longitudinal resistance40 using the anisotropic magnetoresistance effect can well overcome these two bottleneck issues.…”
Section: Electric‐field Control Of Antiferromagnetic Spintronic Devicesmentioning
confidence: 99%
“…Changing their crystal symmetry and relative interatomic distances via stress application can have a substantial impact on the geometrically frustrated magnetic interactions, which in turn strongly change the stability of frustrated and non-frustrated magnetic phases. This is the situation observed in the Mn-based antiperovskite nitride systems Mn 3 GaN and Mn 3 NiN 10, 51,52 . The unstrained form of these two materials show a firstorder PM-to-triangular AFM phase transition at T N 53,54 , shown in Fig.…”
Section: Frustrated Magnetism and Optimal Forms Of The Entropymentioning
confidence: 55%